Allenylidene Complexes Based on Pentacenequinone. Issue 29 (21st August 2013) - Strinitz, Frank; Waterloo, Andreas; Tucher, Johannes; Hübner, Eike; Tykwinski, Rik R.; Burzlaff, Nicolai
Abstract: Stable ruthenium–allenylidene complexes based on pentacenequinone have been synthesized. The complexes show an electronic absorption in the NIR region that arises from forbidden MLCT transitions, as explained by DFT calculations. The crystal structure reveals promising features for the formation of metal‐influenced organic FETs. Abstract : Stable ruthenium–allenylidene complexes based on pentacenequinone have been synthesized. The depicted complex shows an electronic absorption in the NIR region that arises from forbidden MLCT transitions, as explained by DFT calculations. The crystal structure reveals promising features for the formation of metal‐influenced organic FETs.